Tunisia's economic development why better than most of the Middle East but not East Asia - Nabli, Mustapha K. 1948-; Nugent, Jeffrey B. 1936- (Routledge, Taylor & Francis Group, 2023)
Introduction: Tunisia's economic and social outcomes in comparative perspective -- Structural transformation and long term growth in Tunisia and across sample countries -- A historical perspective on Tunisia' development: initial conditions, strategies and policies -- Why has Tunisia been more successful in growth and development than other MENA countries? -- Why has Tunisia not done as well in economic growth and economic development as the most successful East Asian countries? -- A political economy analysis of the balance over time between the roles of the state, markets and the private sector -- Uprisings, democracy and transition.
Hier auch später erschienene, unveränderte Nachdrucke
Includes bibliographical references and index
Keywords: Tunisia / Economic conditions / 1987-; Middle East / Economic conditions; East Asia / Economic conditions